Fri tvang eller tvingende frihet - eller begge deler? - Fjell, Tove Ingebjørg (Tidsskrift for kulturforskning, 2005)
This article deals with the topic of the Norwegian public vaccination programme. Vaccination is voluntary in contemporary Norway, and most people choose to accept the offer from the national public health service. However, discussions are going on internationally as to whether vaccination is a good thing which will lead to better health, or whether it will lead to sickness and even death. Such discussions are also found in this country. The article asks how individuals manage the public’s understanding of risk. In interviews with supporters of the vaccination programme and with sceptics, the motivation for the different choices is focused upon. It is being argued that the public’s understanding of risk and need of control in the case of the vaccination support is being transformed from an external force to an inner sanction, where the individual carries out the discipline. In the case of vaccination scepticism, the resistance towards the programme is characterized by moving authoritative viewpoints from state to other systems of knowledge, where rationality is found i.e. in an alternative arena.